A volume averaged global model study of the influence of the electron energy distribution and the wall material on an oxygen discharge. (16th November 2015) - Toneli, D A; Pessoa, R S; Roberto, M; Gudmundsson, J T
Abstract: A low pressure high density oxygen discharge is studied through a global (volume averaged) model in the pressure range 0.5–100 mTorr. The goal of this work is to evaluate the dependence of collisional energy loss per electron–ion pair created, effective electron temperature, mean density of species, and mean electronegativity on the electron energy distribution function. Differences in the results for Maxwellian and non-Maxwellian distributions show the importance of using a proper electron energy distribution function in discharge modelling. We also explore the differences due to different reactor wall materials comparing the results for an anodized aluminium reactor with a stainless steel reactor. Due to the low recombination coefficient for oxygen atoms on the anodized aluminium walls, the yield of atomic oxygen in anodized aluminium reactors increases significantly as compared to stainless steel reactors. However, the difference of the yield of atomic oxygen in these reactors decreases as pressure increases. Thus, anodized aluminium reactors can be desired for applications where a high concentration of atomic oxygen is required. Finally, the importance of quenching coefficient for plasma modelling is stressed through the quenching coefficient at the walls for ( ). Low quenching coefficients result in high densities of ( ) affecting the mean electronegativity of the plasma due to the decrease in the density of .